The Prehistoric Pueblo World, A.D. 1150-1350 - Adler, Michael A., 1961- (Book collections on Project MUSE., 1996)
Twelve chapters analyze the archaeological record for specific districts and provide a detailed picture of settlement size and distribution, community architecture, and population trends during the period. Additional chapters cover warfare and carrying capacity and provide overviews of change in the region. Throughout the chapters, the contributors address the unifying issues of the role of large sites in relation to smaller ones, changes in settlement patterns from the Pueblo II to Pueblo III periods, changes in community organization, and population dynamics.